Orientalisme dan Penerjemahan Al-Qurâan - Baihaki, Egi Sukma (Jurnal Ilmiah Ilmu Ushuluddin, 2017)
The Quran is believed by Muslims as the last holy book, the revelation of God, and the greatest miracle possessed by the Prophet. The Quran contains values, insights, and science, also contains laws that serve as guidelines for human life. Translation of the Quran is one effort to capture the message of the Quran. The act was also carried out by Orientalists who translated the Quran in different languages for various reasons. Competition, suspicion, and hatred and elements of power cannot be separated from the history of translation of the Quran by the Orientalists. Nevertheless, the paradigm over time began to shift, and made some European intellectuals soft and friendly with Islam, although there are still others who continue to follow in the footsteps of their predecessors.